التخطیط البیئي كآلیة لتحقیق البعد البیئي في إستراتیجیة التنمیة المستدامة - رؤیة مصر 203 - الرميدي, أ.بسام سمير (Finance and Business Economies Review, 2018)
With the increasing problems, risks and negative impacts of projects on the environment, the importance of including the environmental dimension in the planning process has increased, leading to the emergence of so-called environmental planning. The objective of this study is to identify the contribution of environmental planning in achieving the objectives of the strategy of sustainable development - Egypt 2030 in its environmental dimension. The study concluded that the objectives of the environmental dimension in the strategy of sustainable development - Egypt 2030's vision is very much in line with the benefits of environmental planning, as well as the objectives of environmental planning. Therefore, environmental planning will contribute effectively to the achievement of these objectives.